Feminist networks of care in Greece. Practices of resistance from the streets to the screens - Christina Grammatikopoulou (Digital Geography and Society)
Amid Greece's extended economic and socio-political crisis, feminist movements have evolved dynamically to confront the deeply ingrained structures of patriarchy, colonialism, and capitalism that adversely affect women and marginalised communities. This evolution signifies a strategic shift from conventional street protests toward adopting a comprehensive strategy that includes radical care, digital activism, and establishing spaces of solidarity and resistance, both physical and digital. The analysis looks into the transformation of social movements in Greece following the economic crisis, examining them through a lens of care and their manifestations across digital and urban landscapes.It explores the transition from street protests to solidarity initiatives, emphasising how feminist principles both drove and were reinforced by this shift. The discussion extends to the rise of feminist activism over the last decade, highlighting how it incorporates care within the community. Special attention is given to the creation of autonomous spaces by feminist groups, both locally and online, and their efforts to challenge and reshape dominant knowledge systems through hacking initiatives and data practices.